Knowledge Enhancement Among Members of the Women Farmers Group (WFG) through Islamic Science-Based Soil Ecology Education - Delfita, Rina; Helmita, Roza; Haviz, Muhammad; Fajar, Najmiatul; Marneli, Diyyan; Putra, Aidhya Irhash; KF, Dwi Rini; Aini, Latifah Zahra (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
Farmers' knowledge about soil ecology, which is a key factor in increasing the productivity of agricultural products, needs to be evaluated considering that various counseling efforts to increase agricultural yields have not shown satisfactory results. Farmers still unequally manage farmland, providing excessive chemical fertilizers without regard to soil ecology. The purpose of this education is to evaluate the knowledge of the Women's Farmers Group (WFG) before and after conducting soil ecology education based on Islamic science. The subjects of this education were 15 members of WFG Bunga Padi, Jorong Kawai, Nagari Batu Bulek, Lintau Buo Utara, Tanah Datar, West Sumatra, Indonesia. The community-based research (CBR) approach is used in this educational activity. The stages of educational activities start from socialization, laying the basis of the research and the research design, providing pretests and materials, gathering information and analyzing data on biological factors, capillarity of groundwater, water holding capacity, soil aeration, soil fertility, and soil pH, and the evaluation (post-test). The results show an increase in knowledge and understanding among WFG Bunga Padi members after Islamic science-based soil ecology education. It is hoped that, over time, their mindset in managing farmland will be balanced, with less reliance on chemical fertilizers and more emphasis on soil ecology. As a result, Islamic science-based soil ecology education could have a role in improving farmland and laying the foundation for organic farming.